Effect of grinding and aging on subcritical crack growth of a Y-TZP ceramic - Amaral,Marina (2018)
Abstract This study aimed to investigate slow crack growth (SCG) behavior of a zirconia ceramic after grinding and simulated aging with low-temperature degradation (LTD). Complementary analysis of hardness, surface topography, crystalline phase transformation, and roughness were also measured. Disc-shaped specimens (15 mm Ø × 1.2 mm thick, n = 42) of a full-contour Y-TZP ceramic (Zirlux FC, Amherst) were manufactured according to ISO:6872-2008, and then divided into: Ctrl – as-sintered condition; Ctrl LTD – as-sintered after aging in autoclave (134°C, 2 bar, 20 h); G – ground with coarse diamond bur (grit size 181 μm); G LTD – ground and aged. The SCG parameters were measured by a dynamic biaxial flexural test, which determines the tensile stress versus stress rate under four different rates: 100, 10, 1 and 0.1 MPa/s. LTD led to m-phase content increase, as well as grinding (m-phase content: Ctrl – 0%; G – 12.3%; G LTD – 59.9%; Ctrl LTD – 81%). Surface topography and roughness analyses showed that grinding created an irregular surface (increased roughness) and aging did not promote any relevant surface change. There was no statistical difference on surface hardness among different conditions. The control group presented the lowest strength values in all tested rates. Regarding SCG, ground conditions were less susceptible to SCG, delaying its occurrence. Aging (LTD) caused an increase in SCG susceptibility for the as-sintered condition (i.e. G < G LTD < Ctrl < Ctrl LTD).